2018
DOI: 10.1253/circj.cj-18-0082
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Xanthine Oxidoreductase Activity as a Novel Biomarker of Metabolic Disorders in a General Population

Abstract: Plasma XOR activity is a novel biomarker of metabolic disorders in a general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 42 publications
8
84
7
Order By: Relevance
“…It has been suggested that high plasma XOR activity is a metabolic parameter that is superior to uric acid level, and that adequately inhibiting plasma XOR activity unless lowering uric acid would be a new therapeutic strategy for treatment of metabolic and cardiovascular diseases. It has also been reported that unexpected high plasma XOR activities possibly associated with liver dysfunction and insulin resistance are found in some women with a relatively low level of uric acid in a general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that high plasma XOR activity is a metabolic parameter that is superior to uric acid level, and that adequately inhibiting plasma XOR activity unless lowering uric acid would be a new therapeutic strategy for treatment of metabolic and cardiovascular diseases. It has also been reported that unexpected high plasma XOR activities possibly associated with liver dysfunction and insulin resistance are found in some women with a relatively low level of uric acid in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…In a population‐based cohort, the Tanno‐Sobetsu Study, a total of 627 Japanese participants (male/female: 292/335) were recruited from residents of Sobetsu Town in 2016. This population was the same as that in our previous study for investigating plasma XOR activity. Participants treated with any medications were excluded for the elimination of drug effects on plasma XOR activity and adipokines, and participants not taking any medication ( n = 282, male/female: 126/156) were enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, XOR activity should be positively correlated with the serum UA levels because the production of UA requires activation of XOR. While the results of some recent studies support this hypothesis, 11,21,23 other studies report conflicting results. 9,10,22 Nevertheless, although XOR activity and serum UA levels were significantly correlated in the present study, the correlation coefficient was not definitive [r = 0.335 (Spearman), data not shown].…”
Section: Factors Associated With High Xanthine Oxidoreductase Activitmentioning
confidence: 94%